The migraine generator revisited: continuous scanning of the migraine cycle over 30 days and three spontaneous attacks - Schulte, Laura H; May, Arne (Brain (London, England : 1878), 2016)
Functional imaging using positron emission tomography and later functional magnetic resonance imaging revealed a particular brainstem area that is believed to be specifically activated in migraine during, but not outside of the attack, and consequently has been coined the 'migraine generator'. However, the pathophysiological concept behind this term is not undisputed and typical migraine premonitory symptoms such as fatigue and yawning, but also a typical association of attacks to circadian and menstrual cycles, all make the hypothalamus a possible regulating region of migraine attacks. Neuroimaging studies investigating native human migraine attacks however are scarce and for methodological but also clinical reasons there are currently no studies investigating the last 24 h before headache onset. Here we report a migraine patient who had magnetic resonance imaging every day for 30 days, always in the morning, to cover, using functional imaging, a whole month and three complete, untreated migraine attacks. We found that hypothalamic activity as a response to trigeminal nociceptive stimulation is altered during the 24 h prior to pain onset, i.e. increases towards the next migraine attack. More importantly, the hypothalamus shows altered functional coupling with the spinal trigeminal nuclei and the region of the migraine generator, i.e. the dorsal rostral pons during the preictal day and the pain phase of native human migraine attacks. These data suggest that although the brainstem is highly linked to the migraine biology, the real driver of attacks might be the functional changes in hypothalamo-brainstem connectivity.